Analysing Data Sources' Suitability to Support Forest Policy Decision-Making in the Czech Republic. (1st March 2019) - Synek, M.; Hrib, M.
Growing stock, increment, realised felling and potential wood supply are important indicators for strategic policy decision-making in woodbased industry sectors. The aim of the article is to analyse two different data sources, the Forest Management Plans and Guidelines (FMPG) and the National Forest Inventory (NFI), used for the evaluation and prediction of these indicators in the Czech Republic. The differences between the two sources were analysed in terms of their credibility and suitability to support policy decision-making at the state, regional and local levels. Although the FMPG play an important role in policy decision-making, they are not able to determine indicators such as damage inflicted by game, forest regeneration or changes in soil conditions. The NFI, on the other hand, should provide up-to-date results every five years. Unlike the FMPG, where the collected information is reduced, the NFI is a flexible tool for the incorporation of new requirements in measurements.